Pengaruh Harga, Ulasan Produk, Kemudahan dan Keamanan Terhadap Keputusan Pembelian Casing Import di Shopee (Studi Kasus Pada Mahasiswa aktif S-1 Universitas Islam Malang TA 2019/2020) - Ritma Feni Dwy Septant; Nur Hidayati; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this research is to find out and analyze the effect of price, product reviews, convenience and safety on the decision to purchase imported casings at Shopee. Sampling was carried out on active students at the Islamic University of Malang for the 2019/2020 academic year using the Malhotra formula so that a sample of 105 respondents was obtained. This research method uses multiple linear regression analysis with the SPSS analysis tool. This study shows that price, product reviews, convenience and safety have a simultaneous effect on purchasing decisions. Tests carried out with partial tests, all variables have a significant positive effect on the dependent variable. Keywords: Price, Product Reviews, Convenience, Safety, Purchase Decision, Casing, Import